Associations between folate intake and knee pain, inflammation mediators and comorbid conditions in patients with symptomatic knee osteoarthritis - Zhenhua Liu; Ze Chen; Zewei Wu; Mingze Tang; Yongcong Lin; Cuixi Wu; Zhaohua Zhu; Guangfeng Ruan; Changhai Ding; Weiyu Han (BMC Musculoskeletal Disorders)
Abstract Background To investigate the associations between folate intake and changes in knee pain, inflammation mediators and comorbid conditions over 2 years in patients with symptomatic knee osteoarthritis (OA). Methods A post-hoc analysis was performed based on data from the VIDEO study, a multicenter, randomized, double-blind, placebo-controlled clinical trial aimed at assessing the impact of vitamin D supplementation on patients with knee OA who were also vitamin D deficient. The original trial’s design and inclusion and exclusion criteria were integrated into this subsequent post-hoc analysis. The average daily folate intake was evaluated using the Dietary Questionnaire for Epidemiological Studies version 2 over two years. The progression of knee symptoms was monitored at the baseline and then at months 3, 6, 12, and 24, utilizing the Western Ontario and McMaster Universities Index alongside a 100-mm visual analog scale. Levels of serum inflammatory mediators were quantified using ELISA techniques. Assessments of knee joint structures, leg muscle strength, depressive symptoms, feet pain, and low back pain were treated at both baseline and follow-up intervals. Results Folate intake was correlated with reductions in overall knee pain, dysfunction, and stiffness, as well as decreased levels of Leptin and Apelin. Additionally, it was associated with enhanced leg muscle strength and diminished feet and low back pain. However, there is no association between folate intake and alterations in serum cytokine levels or knee joint structural changes. Within the subsets of overall knee pain, a significant relationship was identified between folate intake and the reduction of pain experienced when ascending or descending stairs and standing for two years. Conclusions Folate intake was linked with reduced knee pain, lower levels of adipokines, and a decreased prevalence of comorbid conditions in individuals with knee OA, implying that folate consumption may be associated with an improvement in knee OA symptoms, but further research is needed to verify this association.